UTILIZATION OF THE INTERNET BY USING SMARTPHONES TO INCREASE STUDENT INSIGHTS IN MADRASAH ALIYAH MAWADDI, KECAMATAN BANJARAN DISTRICT, BANDUNG REGENCY - Tom Finaldin (Hubungan Internasional, 2020)
ABTRACT: The use of smartphones in Madrasah Aliyah Mawaddi, Banjaran District, Bandung Regency has not been able to increase students' insights to support the knowledge they have gained from school through textbooks. Students are only just actively using it to the extent of chatting, taking selfies, and playing games, both online and offline. Researchers feel interested in further researching this phenomenon using qualitative methods. Data taken through observation and interviews with students and teachers. The results of the study are the researchers found that students have not been able to use smartphones to broaden their horizons due to several things, namely: lack of information about using the internet for productive activities, lack of encouragement from teachers to utilize the internet, lack of student focus on their ideals, lack of time due must help their parents, and the weak economic situation of the family. The conclusion that can be drawn is the use of the internet through the use of smartphones is still not optimal due to lack of information, motivation, time, and weak purchasing power of students. Suggestions that can be given are students must be given information through training and teacher encouragement; familiarize learning by utilizing the internet; economic assistance for parents of students.Keywords: Internet-Smartphone-Students